1998
DOI: 10.1021/cr970002a
|View full text |Cite
|
Sign up to set email alerts
|

Hemiporphyrazines as Targets for the Preparation of Molecular Materials:  Synthesis and Physical Properties

Abstract: ContentsI. Introduction 563 II. Synthesis 564 A. Hemiporphyrazines 564 B. Triazolehemiporphyrazines 569 C. Other Hemiporphyrazines 570 III. Molecular Organization of Hemiporphyrazines in Condensed Phases 571 IV. Hemiporphyrazines as Units for Molecular Organic Materials 573 V. Concluding Remarks 574 VI. Acknowledgments 574 VII. References 574

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 78 publications
2
83
0
Order By: Relevance
“…[6,7] Various aspects of their synthesis, structure particularities, coordination characteristics, and practical applications have been reviewed. [8][9][10][11] New optical limiting [12] and photophysical properties [13][14][15] of Hps have also been reported. Therefore multiloop conjugation systems, which can be highlighted in Hps molecules, stimulate considerable theoretical interest.…”
Section: Introductionmentioning
confidence: 91%
“…[6,7] Various aspects of their synthesis, structure particularities, coordination characteristics, and practical applications have been reviewed. [8][9][10][11] New optical limiting [12] and photophysical properties [13][14][15] of Hps have also been reported. Therefore multiloop conjugation systems, which can be highlighted in Hps molecules, stimulate considerable theoretical interest.…”
Section: Introductionmentioning
confidence: 91%
“…[1,2] In 1960-70 th MHCC containing combination of isoindole fragments with benzene rings were most actively studied in the USSR because of their potential application properties. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Thus, it was reported that the copper(II) complex of cyclo-1,3-phenylenetriisoindole ("Stabilin-9") (1a) can be used as stabilizer of polycaproamide, [5] as fire-retarding and antioxidant agent. [6] Besides, there are data on possible application MHCC as pigments, [3] dyes, [7] thermo-and light stabilizers of polymeric materials, [4,8,9] catalysts in a number of chemical and electrochemical oxidation-reduction processes, [4,9,10] inhibitors of siloxane polymers burning.…”
Section: Sulfur Containing Macroheterocyclesmentioning
confidence: 99%
“…in place of benzene rings were more actively studied and their synthesis and properties were reviewed. [14][15][16][17] Heating the mixture of o-carboxybenzenesulfinic acid 5, urea, copper(I) chloride and ammonium molybdate with gradual increase of temperature from 130 to 180 and finally to 210 0 C they have obtained the olive product 2 which was named Cu-tetrabenzotetrathioporphyrazine or Cu tetrathiophthlocyanine. [23] Unlike Cu phthalocyanine which can be obtained similarly from phthalic acid derivatives, its tetrathioanalogue 6a is soluble in the majority of organic solvents.…”
Section: Sulfur Containing Macroheterocyclesmentioning
confidence: 99%
“…[64][65][66][67][68][69] In order to satisfy this demand, over the last few decades numerous research groups have made great strides in the preparation of asymmetric phthalocyanines and their analogues including triazole-, thiadiazole-, and hemiporphyrazines. [64][65][66][67][68][69][70][71][72][73][74] The chemistry of asymmetric phthalocyanines had a slow start. The first report on an asymmetric phthalocyanine analogue by Linstead and co-workers dates back to 1955, 75 followed by work of Luk'yanets and co-workers in 1979.…”
Section: Introductionmentioning
confidence: 99%